Is the rise in childhood obesity rates leading to an increase in hospitalizations due to dengue? - Jeewandara, Chandima; Karunananda, Maneshka Vindesh; Fernando, Suranga; Danasekara, Saubhagya; Jayakody, Gamini; Arulkumaran, Segarajasingam; Samaraweera, Nayana Yasindu; Kumarawansha, Sarathchandra; Sivaganesh, Subramaniyam; Amarasinghe, Priyadarshanie Geethika; Jayasinghe, Chintha; Wijesekara, Dilini; et al. (PLOS Neglected Tropical Diseases, 2024)
Background Obesity and diabetes are known risk factors for severe dengue. Therefore, we sought to investigate the association of obesity with increased risk of hospitalization, as there is limited information. Methods and findings Children aged 10 to 18 years (n = 4782), were recruited from 9 districts in Sri Lanka using a stratified multi-stage cluster sampling method. Details of previous admissions to hospital due to dengue and anthropometric measurements were recorded and seropositivity rates for dengue were assessed. The body mass index (BMI) centile in children aged 10 to 18, was derived by plotting the values on the WHO BMI-for-age growth charts, to acquire the percentile ranking. Results Although the dengue seropositivity rates were similar in children of the different BMI centiles, 12/66 (18.2%) seropositive children with a BMI centile >97th, had been hospitalized for dengue, compared to 103/1086 (9.48%) of children with a BMI centile of <97th. The logistic regression model suggested that BMI centiles 50th to 85th (OR = 1.06, 95% CI, 1.00 to 1.11, p = 0.048) and BMI centile of >97th (OR 2.33, 95% CI, 1.47 to 3.67, p = 0.0003) was significantly associated with hospitalization when compared to children in other BMI categories. Conclusions Obesity appears to be associated with an increased risk of hospitalization in dengue, which should be further investigated in longitudinal prospective studies. With the increase in obesity in many countries, it would be important to create awareness regarding obesity and risk of severe disease and hospitalization in dengue.